2016
DOI: 10.1590/1516-4446-2014-1640
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of hallucinations in bipolar disorder

Abstract: Objective: Approximately one-half of all patients affected by bipolar disorder present with psychotic features on at least one occasion. Several studies have found that alterations in the activity of mesolimbic and prefrontal regions are related to aberrant salience in psychotic patients. The aim of the present study was to investigate the structural correlates of a history of hallucinations in a sample of euthymic patients with bipolar I disorder (BD-I). Methods: The sample consisted of 21 euthymic patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
0
16
1
2
Order By: Relevance
“…To our knowledge, this is the first study to investigate brain structural correlates of auditory hallucinations in BD. Our regional findings differed from the results from two previous studies that reported divergent findings of reduced grey matter volume in the left middle temporal gyrus, and reduced grey matter density in the right insula between BD patients with hallucinations of any modality and patients without hallucinations. Discrepancies in findings could be attributed to small sample sizes, and differences in group characteristics (hallucinations or auditory hallucinations).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first study to investigate brain structural correlates of auditory hallucinations in BD. Our regional findings differed from the results from two previous studies that reported divergent findings of reduced grey matter volume in the left middle temporal gyrus, and reduced grey matter density in the right insula between BD patients with hallucinations of any modality and patients without hallucinations. Discrepancies in findings could be attributed to small sample sizes, and differences in group characteristics (hallucinations or auditory hallucinations).…”
Section: Discussioncontrasting
confidence: 99%
“…The observed thicker cortex in the BD+ group could also be related to structural plasticity, such as increased neuronal size, increased number of dendritic spines, increased number of glial cells and increased vascularization and regional blood flow . Neves et al suggested that the grey matter density reduction they observed in the insula in BD patients with hallucinations supported the hypothesis that aberrant salience might underlie psychotic symptoms in BD. It could be speculated that thicker cortex in regions involved in sensory processing is associated with structural abnormalities facilitating sensory processing, either because of, or as a contributing cause of, inappropriate salience towards internal and external stimuli.…”
Section: Discussionmentioning
confidence: 90%
“…The salience network is proposed to facilitate access to these attentional and working memory systems by dynamically switching from engagement of the internally oriented default mode network (DMN) to the task-oriented central executive (i.e., frontoparietal control) network (82). Psychosis is believed to reflect a state of aberrant salience (84), in part, and structural abnormalities in the salience network have been linked to reality distortion in the form of hallucinations (85, 86) and delusions (85). A previous study reported reduced FC between cerebellar and salience networks in schizophrenia, but not in BP (56); however, the BP sample consisted of clinically stable outpatients, and it is unclear what proportion of those BP patients had histories of psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies found greater GMVs in the right DLPFC, left inferior frontal gyrus, right parieto-occipital area, and left fusiform gyrus (Ekman et al, 2017) or negative findings (Neves Mde et al, 2016) in P-BD patients relative to NP-BD patients. Using the whole-brain analysis, the studies reported greater GMVs in the left superior frontal gyrus, right middle frontal gyrus, left ACC, right precentral gyrus, precuneus, and caudate body in P-BD patients compared with NP-BD patients .…”
Section: P-bd Versus Np-bd Patientsmentioning
confidence: 74%
“…Finally, a total of 37 studies were included in this systematic review (Figure 1), most of which enrolled a HC group, except for 6 studies (Foland-Ross et al, 2011;Haukvik et al, 2015;Hibar et al, 2018;Neves Mde et al, 2016;Radaelli et al, 2014;Stanfield et al, 2009) that merely compared P-BD with NP-BD patients. After reviewing the titles and abstracts, 1,779 citations were discarded since they did not meet our inclusion criteria.…”
Section: Included Studies and Sample Characteristicsmentioning
confidence: 99%